The clinical effectiveness of ginger compared to vitamin B6 in reducing hyperemesis gravidarum: Systematic review - Pragastiwi, Enggar Avilia; Anjar Wati, Intan Arum; Sari, Siti Nurul Fadhilah; Lubis, Pahyuri; Mufdlilah, Mufdlilah; Listiani, Putri (Universitas Aisyiyah Yogyakarta, 2024)
Introduction: Hyperemesis gravidarum refers to an extreme condition of nausea and vomiting that occurs during pregnancy. Nausea and vomiting that harm the mother differ from morning sickness, commonly experienced in early trimester pregnant women. Approximately 14.8% of pregnancies experience symptoms of nausea and vomiting, with occurrence rates ranging from 60-80% among first-time mothers (primigravidas) and 40-60% among women who have had multiple pregnancies (multigravidas). These symptoms become more severe in one in a thousand pregnancies. Purpose: This study aimed to systematically review Ginger's effectiveness compared to vitamin B6 in reducing hyperemesis gravidarum. Method: This is a systematic review of three databases (PubMed, ScienceDirect, and Willey online library). The PRISMA-ScR protocol was employed in this research review, utilizing a Population, Intervention, Comparison, and Outcome (PICO) framework. The population is first-trimester pregnant women who experience Hyperemesis gravidarum using a completely original research article comparing Ginger and vitamin B6 in reducing hyperemesis gravidarum. Results: A significant statistical distinction was observed between the Ginger and the vitamin B6 group concerning the nausea score (mean difference 0.63, CI -0.10-1.35) and vomiting score (mean difference 0.42, CI -0.13, 0.98). Conclusion: Based on the research results, there was no significant difference in the effectiveness of giving Ginger compared to vitamin B6 in reducing hyperemesis gravidarum. However, the analysis showed that the average score of giving Ginger was lower than vitamin B6. The lower the nausea or vomiting score, the better the effect of the intervention. Suggestion: Health workers (doctors and midwives) can use Ginger as an alternative to reduce hyperemesis gravidarum during early pregnancy.